Construction of a database of aromatic medicinal plants from the Baixo Tocantins Region, Amazon, Pará, Brazil: preliminary results (Research, Society and Development, 2022)
The construction of a database of aromatic medicinal plants (BDPMA) is extremely important for the documentation of Tocantina biodiversity. In this context, this research aimed to build a BDPMA for six rural communities in the Baixo Tocantins region, Pará, Brazil. In total, 241 exsiccates were made and of this total, 36 (14.9%) were classified as aromatic medicinal plants and the most representative botanical family was Lamiaceae. The computerization of these ethnobotanical data will be essential for the implementation of actions aimed at preserving and sharing important information for basic and applied research in several areas of knowledge.